Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.jorganchem.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Two substrates, three products: Reactions between ferrocene-carboxaldehyde and dioxaphospholene, characterization and crystal structures of oxygenated C3- and C4-chain-containing ferrocenes

Abstract: Reactions of aldehydes RCHO with 2,2,2-trimethoxy-4,5-dimethyl-1,3,2dioxaphospholene are known to form trimethylbiacetyl-aldehyde-phosphite adducts which upon methanolysis gave rise to the corresponding symmetrical 3-R-2,4-pentanediones (R = aryl, alkyl). Reactions between ferrocenecarboxaldehyde and the biacetyl-trimethylphosphite adduct, whatever the experimental conditions used, afforded three new oxygenated C 3 and C 4 side-chain containing ferrocenyl complexes, namely, 1-ferrocenyl-1,2-propanedione (1, Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Very recently, we have shown that in the reaction between ferrocenecarboxaldehyde with a slight excess (15%) of 2,2,2-trimethoxy-4,5-dimethyl-1,3,2-dioxaphospholene, under Ramirez's conditions or slightly modified conditions, ferrocenecarboxaldehyde behaves very differently from aromatic aldehydes [11]. The expected symmetrical target compound 3ferrocenyl-2,4-pentanedione is, indeed, never obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, we have shown that in the reaction between ferrocenecarboxaldehyde with a slight excess (15%) of 2,2,2-trimethoxy-4,5-dimethyl-1,3,2-dioxaphospholene, under Ramirez's conditions or slightly modified conditions, ferrocenecarboxaldehyde behaves very differently from aromatic aldehydes [11]. The expected symmetrical target compound 3ferrocenyl-2,4-pentanedione is, indeed, never obtained.…”
Section: Methodsmentioning
confidence: 99%